Another Thing to Fall - Laura Lippman 1959- (New York William Morrow and Company, 2008)
When the production of a Hollywood film in Baltimore brings mayhem and murder to the area, private investigator Tess Monaghan finds her job complicated by the acting skills of her numerous suspects.
Keywords: Literature (3GdCOHs; General -- Fiction; Monaghan, Tess (Fictitious character); Television -- Production and direction -- Fiction; Actresses -- Fiction; Women private investigators -- Maryland -- Baltimore -- Fiction